Cerebrospinal fluid markers of neuroinflammation in delirium: A role for interleukin-1ß in delirium after hip fracture - CUNNINGHAM, COLM (My University, 2014)
Objective Exaggerated central nervous system (CNS) inflammatory responses to peripheral stressors may be implicated in delirium. This study hypothesised that the IL-1β family is involved in delirium, predicting increased levels of interleukin-1β (IL-1β) and decreased IL-1 receptor antagonist (IL-1ra) in the cerebrospinal fluid (CSF) of elderly patients with acute hip fracture. We also hypothesised that Glial Fibrillary Acidic Protein (GFAP) and interferon-γ (IFN-γ) would be increased, and insulin-like growth factor 1 (IGF-1) would be decreased. Methods Participants with acute hip fracture aged > 60 (N = 43) were assessed for delirium before and 3–4 days after surgery. CSF samples were taken at induction of spinal anaesthesia. Enzyme-linked immunosorbent assays (ELISA) were used for protein concentrations. Results Prevalent delirium was diagnosed in eight patients and incident delirium in 17 patients. CSF IL-1β was higher in patients with incident delirium compared to never delirium (incident delirium 1.74 pg/ml (1.02–1.74) vs. prevalent 0.84 pg/ml (0.49–1.57) vs. never 0.66 pg/ml (0–1.02), Kruskal–Wallis p = 0.03). CSF:serum IL-1β ratios were higher in delirious than non-delirious patients. CSF IL-1ra was higher in prevalent delirium compared to incident delirium (prevalent delirium 70.75 pg/ml (65.63–73.01) vs. incident 31.06 pg/ml (28.12–35.15) vs. never 33.98 pg/ml (28.71–43.28), Kruskal–Wallis p = 0.04). GFAP was not increased in delirium. IFN-γ and IGF-1 were below the detection limit in CSF. Conclusion This study provides novel evidence of CNS inflammation involving the IL-1β family in delirium and suggests a rise in CSF IL-1β early in delirium pathogenesis. Future larger CSF studies should examine the role of CNS inflammation in delirium and its sequelae.
PUBLISHED
Keywords: Delirium; Cerebrospinal fluid; Inflammation; Interleukin-1β; Interleukin-1 receptor antagonist; Delirium; Cerebrospinal fluid; Inflammation; Interleukin-1β; Interleukin-1 receptor antagonist